Pengaruh Model Discovery Learning Terhadap Hasil Belajar Matematika Siswa SDN Gugus 19 Kota Bengkulu - Betri Melinda; Sri Ken Kustianti; Victoria Karjiyati (Universitas Bengkulu, 2021)
This study aims to determine the effect of Discovery Learning model on student learning outcomes in learning Mathematics in class V in SDN Gugus 19 Kota Bengkulu 2017/2018 lesson year. This research is a quantitative research. The research design used was Quasi Experimental Design with design type The Matching Only Pretest-Posttest Control Group Design. The test is done twice before and after the treatment in the sample class. The population of this research is all students of class V in SD Negeri Gugus 19 Kota Bengkulu using Curriculum 2013. The sampling technique using Cluster Random Sampling, The sample in this research is class V SD Negeri 71 Kota Bengkulu as experiment group and class V SD Negeri 72 Kota Bengkulu as a control group. Instrument research in the form of learning result test. Based on the results of the hypothesis by using t-test at concluded that there is an influence of the Discovery Learning model on student learning significance level 5% obtained t calculate 13.57> t table 1.67. Thus it can be outcomes in learning Mathematics in class V at SDN Gugus 19 KotaBengkulu